Practice surrounding adverse events in residential care facilities in Ireland. (20th October 2021) - McGrane, N; Dunbar, P; Dunnion, M; O'Connor, L
Abstract: Background: Part of regulation of residential care facilities (RCFs) is the statutory responsibility of RCFs to notify the regulator about adverse events (AEs). Notifications typically include a description of practice in the aftermath of AEs and are an information source that can inform quality and safety improvements. The herein aim therefore was to analyse narratives in notifications received by the Health Information and Quality Authority (HIQA) in Ireland, to identify practice surrounding AE management and reporting. Methods: A sample (n = 447) of notifications received by HIQA in 2018 was drawn from the Database of Statutory Notifications from Social Care in Ireland, 2013-2019. Inductive thematic analysis was conducted. Analysis was structured using the a priori agreed themes of: practice in the aftermath of an AE, system vulnerabilities and reporting practices. Results: Two overarching themes were identified. The first, a chronological theme contained three sub-themes: pre event, including existing measures and situations, response to the event and continued response. Measures that are resident focused and follow policies and protocols in RCFs to prevent or mitigate the seriousness of AEs, were evident in the response and continued response. From this chronological order emerged the cyclical theory where short and longer term actions become part of the pre-event of future similar or repeated AEs. The second overarching theme, regulatory input, encapsulated procedural notes, requests for further information and notes on repetitive patterns. Conclusions: RCFs respond to AEs with short and longer term actions with resident health and wellbeing as the focus. These actions in turn become part of the pre-event of future AEs. This cycle can be leveraged for quality improvement initiatives. Input from inspectors was positive and constructive but highlighted some regulatory burden. Dissemination of these results as good practice guides may improve management and reporting of AEs. Key messages: Residential care facilities respond to adverse events with short and long term measures which feed into the management of future AEs. This cycle can be leveraged for quality improvement initiatives. Improvement opportunities in reporting practices were found. The development of good practice guides for residential care facilities and inspectors could reduce regulatory burden.